2017
DOI: 10.1016/j.pmedr.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in receipt of 5As for smoking cessation in diverse primary care and HIV clinics

Abstract: Clinical practice guidelines recommend that clinicians implement the 5As (Ask, Advise, Assess, Assist, and Arrange) for smoking cessation at every clinical encounter. We sought to examine the prevalence of patient- and clinician-reported 5As in two primary care and one HIV care clinics in San Francisco, California between August 2013 and March 2014 (n = 462 patients and n = 61 clinicians). We used multivariable logistic regression analysis to identify factors associated with receipt of the 5As, adjusting for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
1
28
2
Order By: Relevance
“…This rate is quite remarkable when compared with self-reported 5As receipt rates from smoking patients in some primary care settings: Ask (50%-80%), Advise (27%-77%), Assess (41%-63%), Assist (41%-56%), and Arrange (10%-22%). [25][26][27] Similarly, the iMD administration seems to yield more favorable results in comparison with California statewide data, which suggest that only 54% Korean and 64% Vietnamese smokers received provider advice in the past 12 months. 28 The multivariable logistic regression results showed that the intervention visits with iMD administration had particularly higher rates of EHRdocumented 5As deliveries, especially in assessing patients' readiness for quitting, assisting patients with quitting, and arranging for follow-ups, when compared with other PCP visits without iMD administration.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This rate is quite remarkable when compared with self-reported 5As receipt rates from smoking patients in some primary care settings: Ask (50%-80%), Advise (27%-77%), Assess (41%-63%), Assist (41%-56%), and Arrange (10%-22%). [25][26][27] Similarly, the iMD administration seems to yield more favorable results in comparison with California statewide data, which suggest that only 54% Korean and 64% Vietnamese smokers received provider advice in the past 12 months. 28 The multivariable logistic regression results showed that the intervention visits with iMD administration had particularly higher rates of EHRdocumented 5As deliveries, especially in assessing patients' readiness for quitting, assisting patients with quitting, and arranging for follow-ups, when compared with other PCP visits without iMD administration.…”
Section: Discussionmentioning
confidence: 95%
“…One study found that patients with cardiovascular conditions were more likely to report receipt of Assist and Arrange by patients' self-report. 26 Another study based on EHR-documented 5As reported that older age was associated with Assist documentation; however, no meaningful analysis could be further conducted on Arrange delivery due to so few Arrange documented (2% out of 1200 progress notes reviewed). 23 Both age and comorbid health conditions were adjusted in our multivariable analyses (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning, since 40 percent of patients with HIV smoke and smoking has a strong effect on morbidity and mortality in this group . Reasons for this disparity are unclear, but it has been observed elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…30,31 Reasons for this disparity are unclear, but it has been observed elsewhere. 32 This study is the first to examine rates of smoking documenta- about tobacco use in 2013-2014. 35 Like our study, both of these studies found that smoking documentation was significantly more common for patients with comorbidities than for those without.…”
Section: Discussionmentioning
confidence: 99%
“…The number of physicians who ask about smoking status varies widely (33%–65%), and fewer physicians assist patients with smoking cessation counseling. 4346 When patients enter treatment for MHSUP, it provides an opportunity to identify smokers (nondaily and daily) and provide cessation treatment options.…”
Section: Discussionmentioning
confidence: 99%